A Study on the MSME Growth of Pisang Uhuyy Bengkalis and Telou Gulung Yung Dollah at Polbeng Business Expo Chapter II - Zulaika Zulaika; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Polbeng Business Expo Chapter II is an event organized by students of the International Business Administration Study Program at Bengkalis State Polytechnic with the theme Local Innovation Impact Global. This event involved 133 tenants from various business fields and aimed to provide direct business practice experience while supporting the development of Micro, Small and Medium Enterprises (MSMEs). During the event, the author played a role in assisting the development of Pisang Uhuyy Bengkalis and Telou Gulung Yung Dollah MSMEs through various business development programs, such as creating profile videos, promotional videos, product catalogs, implementing digital marketing through social media, creating a QRIS payment system, and compiling financial reports during the expo. These programs have proven effective in enhancing product appeal, expanding marketing reach, simplifying consumer transaction processes, and assisting MSMEs in managing their finances more efficiently. By participating actively in this vibrant exhibition, students gained invaluable practical insights into operational strategies and current market demands. Additionally, the targeted mentoring approach significantly boosted the daily sales volume and long term sustainability prospects for both of the assisted local food vendors during the festival. Overall, the implementation of the Polbeng Business Expo Chapter II has had a positive impact on increasing business visibility, facilitating transactions, and improving financial management for MSMEs, thereby supporting business growth and development.